KEBIJAKAN PEMERINTAH KOTA JAKARTA SELATAN DALAM PENGELOLAAN SAMPAH MENURUT PERATURAN DAERAH NOMOR 3 TAHUN 2013 DI KECAMATAN PASAR MINGGU: Government Policy of South Jakarta City in Waste Management According to Regional Regulation No. 3 of 2013 in Pasar Minggu District - Muhammad Alfiansyah Rasyid; Irene Mariane (Reformasi Hukum Trisakti, 2025)
The Jakarta Provincial Government has granted authority to the Regional Government to manage waste comprehensively, including in the Pasar Minggu District, South Jakarta. This article how law enforcement regarding waste management in Pasar Minggu District is implemented in accordance with Regional Regulation Number 3 of 2013 concerning Waste Management. The research problem focuses on identifying the obstacles in enforcing sanctions for violations of waste disposal regulations in Pasar Minggu District, South Jakarta. This study is normative juridical in nature and descriptive in character, with conclusions drawn using deductive reasoning. The findings indicate that the enforcement of sanctions often faces obstacles due to a lack of human resources, inadequate supporting facilities, and community resistance to waste management. Therefore, the Regional Government needs to optimize waste management by strengthening education, enhancing supervisory capacity, providing adequate facilities, and adopting a holistic approach to increase community participation and the effectiveness of law enforcement, in order to achieve sustainable waste management and a cleaner environment in Pasar Minggu District.